Features of the Functioning of Public Opinion in the Context of Postmodernism - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
Building a democratic state governed by the rule of law is inextricably linked with the need to act in accordance with public interests and moral norms, which is directly reflected in public opinion. The latter, as an independent element of social life, is one of the possible conditions for the existence of democracy, as well as an indicator of its development. The article examines the features of the functioning of public opinion in the context of postmodernism, the study of which makes it possible to identify problems in public life, to avoid manipulating public opinion.